Background analog and mixed signal calibration system for time-interleaved ADC. Issue 7 (July 2015) - Khalil, Raouf; Louërat, Marie-Minerve; Petigny, Roger
Abstract In this work, a novel background calibration technique for time-interleaved analog-to-digital converters (ADCs) is proposed. The offset, gain, time skew and bandwidth mismatches are considered and analyzed in detail, highlighting the efficiency of the proposed calibration method. The calibration system is an analog mixed one where the error detection is performed digitally by three detectors: offset detector, amplitude detector and phase detector. The correction is performed in both the analog and the digital domains. We have proposed a calibration sequence that allows us to distinguish between the different errors, resulting in high accuracy detection and correction phases. The efficiency and the accuracy of the calibration technique are verified through <alternatives><inline-graphic xlink:href="ark:/27927/pgjrr1rfcs" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />MATLAB®</alternatives> and VHDL-AMS simulations.